(untitled) (NTU Journal of Agriculture and Veterinary Science, 2021)
This study was carried out at animals house–college of veterinary medicine university of Mosul aimed to identify the effect of acclimation and adding vitamin C to drinking water of local hens reared under hot climate in some physiological traits and production performance. One hundred twenty unsexed one day old (local chicks) were divided into two divisions, the first division reared on ordinary condition and called not acclimated and other division also reared on ordinary condition yet exposed to (39 ±2)°C temperature for six hours daily at age (6, 9, 12 and 15) days to acclimate them to high temperature and called acclimated. At (22) days old birds were divided into four treatments in each treatment thirty chicks with three replicate (ten birds in each). The treatments were as follows T1 Control (An acclimated), T2 Acclimated, T3 An acclimated and adding 150 mg Vit. C / Litter drinking water,T4 Acclimated and adding 150 mg Vit. C / Litter drinking water. Birds reared under cyclic temperature (25 -36 -25)°C in semi-opened houses until 56 days old. Statistical analysis of data showed a significant increase in Hetero., Lympho., Mono., Baso., Esino., pH, Hb, RBC, WBC, PCV, weight gain, body weight at slaughter, carcass weight, Relative weight of Gizzard, Spleen and Liver weight for birds of T4. Improving in Heat Tolerance in T3 and T4. No significant differences between treatments in Initial body weight, Relative Heart weight and Body Temperature.